Mode of Cell Wall Growth of Bacillus megaterium - Mauck, J. (1972)
The growth of the cell wall of Bacillus megaterium KM was examined by labeling the cell wall uniformly with (3)H-α, ε-diaminopimelic acid and examining by radioautography the distribution of labeled cell wall material in daughter cells. The results indicate that the label is distributed uniformly to all daughter cells and rule out a single growth point, either central or apical, for these cells. The results strongly suggest that cell wall growth occurs by uniform deposition of new wall over the whole cell surface.